ESTABLISHMENT OF A SYSTEM OF INDICATORS FOR TRANSFORMING THE REGIONAL FARM OF BULGARIA TOWARDS THE BIOECONOMY IN THE CONTEXT OF BIOMASS - D. Toteva; R. Popov; P. Marinov (Trakia Journal of Sciences)
The bioeconomy includes all sectors and systems that rely on biological resources (animals, plants, micro-organisms and biomass, including organic waste), their functions and principles. The use of new technologies in the national economy is a key moment, which will create opportunities for the production of high - quality products from bioeconomy represented by the different types of activities. In the paper presents some of the basic indicators (socio-economic) applicable in the regional economy of the country, based on the principles and factors specific to each region. The transformation of indicators towards the bioeconomy will give greater opportunities for social and economic prosperity in each region of the country according to its specific characteristics. Biomass is a kind of solar energy conserved in plant and animal organisms. Biomass as a resource includes waste products from animals and human activities. On earth, there is a certain amount of "dead" organic matter that can be used once as a non-renewable resource from organic fuels.